Morphology–Function Relationship of Thermoelectric Nanocomposite Films from PEDOT:PSS with Silicon Nanoparticles. (4th July 2017) - Saxena, Nitin; Čorić, Mihael; Greppmair, Anton; Wernecke, Jan; Pflüger, Mika; Krumrey, Michael; Brandt, Martin S.; Herzig, Eva M.; Müller‐Buschbaum, Peter
Abstract : The relation of the thermoelectric figure of merit and the nanocomposite morphology is studied for thermoelectric thin films consisting of poly(3, 4‐ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) with different amounts of silicon nanoparticles (Si‐NPs). An increase in the figure of merit of up to 150% is found for an Si‐NP concentration of 0.5 wt% as compared to pristine PEDOT:PSS films. The improvement originates from a disruption in the molecular ordering and therefore reduced electrical conductivity, which leads to an increased Seebeck coefficient, while also reducing thermal conductivity for higher concentrations through phonon scattering. The thermal conductivity is measured with steady‐state IR thermography on free‐standing PEDOT:PSS/Si‐NP composite films, enabling a full determination of the figure of merit. The morphology is investigated with grazing incidence resonant tender X‐ray scattering (GIR‐TeXS) around the sulfur K‐absorption edge. Without need for extrinsic labeling, GIR‐TeXS measurements have varying scattering contrast conditions for the components of the ternary system. By comparing the scattered intensities at different photon energies with the corresponding scattering contrast, the Si‐NPs are found to be preferentially dispersed in the large and medium‐sized PEDOT‐rich domains. The changes in size for the PEDOT‐rich domains as function of Si‐NP concentration cause improvement of the thermoelectric properties of the films. Abstract : The morphology–function relationship of thermoelectric nanocomposite films from PEDOT:PSS with silicon nanoparticles is discussed. True in‐plane thermal conductivity is measured via steady‐state infrared thermography enabling calculation of figure of merits. An increase in the figure of merit is found for low nanoparticle concentrations and ascribed to morphological changes of the nanocomposite films as determined with grazing incidence resonant tender X‐ray scattering.